2019
DOI: 10.1002/mp.13704
|View full text |Cite
|
Sign up to set email alerts
|

Broadband lung dielectric properties over the ablative temperature range: Experimental measurements and parametric models

Abstract: Purpose Computational models of microwave tissue ablation are widely used to guide the development of ablation devices, and are increasingly being used for the development of treatment planning and monitoring platforms. Knowledge of temperature‐dependent dielectric properties of lung tissue is essential for accurate modeling of microwave ablation (MWA) of the lung. Methods We employed the open‐ended coaxial probe method, coupled with a custom tissue heating apparatus, to measure dielectric properties of ex viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…The results indicated that the dielectric properties of human cancer tissues and the corresponding normal tissues are often quite different. On the basis of this difference, a variety of diagnostic and therapeutic techniques have been developed, including magnetic resonance electric properties tomography (MR‐EPT) [Liu et al, ; Ariturk and Ider, ], surgical margin detection [Summers et al, ], and microwave ablation [Sebek et al, ], etc. In this article, we use this method to measure the dielectric properties of ex vivo metastatic and non‐metastatic lymph nodes (LNs) from lung cancer surgeries, including pre‐vascular and retrotraccheal LNs, subaortic LNs, para‐aortic LNs, subcarinal LNs, paraesophageal LNs, pulmonary ligament LNs, hilar LNs, and interlobar LNs.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the dielectric properties of human cancer tissues and the corresponding normal tissues are often quite different. On the basis of this difference, a variety of diagnostic and therapeutic techniques have been developed, including magnetic resonance electric properties tomography (MR‐EPT) [Liu et al, ; Ariturk and Ider, ], surgical margin detection [Summers et al, ], and microwave ablation [Sebek et al, ], etc. In this article, we use this method to measure the dielectric properties of ex vivo metastatic and non‐metastatic lymph nodes (LNs) from lung cancer surgeries, including pre‐vascular and retrotraccheal LNs, subaortic LNs, para‐aortic LNs, subcarinal LNs, paraesophageal LNs, pulmonary ligament LNs, hilar LNs, and interlobar LNs.…”
Section: Introductionmentioning
confidence: 99%
“…According to the 4thorder Cole-Cole model, the dielectric constant and electrical conductivity of the lung tissue at the end of expiration and inhalation at 2.45 GHz were calculated. The Cole-Cole model is described as follows [20]:…”
Section: Tissue Ablation Governing Equationsmentioning
confidence: 99%
“…The overall measurement setup is depicted in Figure 3.1(a). The temperature sensor was placed 2 mm away from the dielectric probe tip to preclude interference with electromagnetic field of the probe [63] as shown in Figure 3.1(b). A polyimide sheath was slid over the fiber optic sensor for its protection and a rubber band was used to fix the sensor at an appropriate position over the dielectric probe.…”
Section: Measurement Of Dielectric Propertiesmentioning
confidence: 99%
“…The fibroid sample was taken out from the RPMI gauze and placed in a custom-designed sample holder shown in Figure 3.1(c). The sample holder was constructed from copper sheets with the objective of minimizing thermal gradients across the sample, similar to prior studies [63], [135]. First, the dielectric properties were recorded at room temperature (23 ºC).…”
Section: Measurement Of Dielectric Propertiesmentioning
confidence: 99%
See 1 more Smart Citation